A novel dopamine electrochemical sensor based on La3+/ZnO nanoflower modified graphite screen printed electrode - Somayeh Tajik; Hadi Beitollahi; Mohammad Reza Aflatoonian (Journal of Electrochemical Science and Engineering, 2019)
Flower-like La3+/ZnO nanocomposite was facile synthesized. A simple and ultrasensitive sensor based on graphite screen printed electrode (SPE) modified by La3+/ZnO nanoflower was developed for the electrochemical determination of dopamine. The electrochemical behavior of dopamine was studied in 0.1 M phosphate buffer solution (PBS) using cyclic voltammetry (CV), chronoamperometry (CA) and differential pulse voltammetry (DPV). Compared with the unmodified graphite screen printed electrode, the modified electrode facilitates the electron transfer of dopamine, since it notably increases the oxidation peak current of dopamine. Also, according to CV results the maximum oxidation of dopamine on La3+/ZnO/SPE occurs at 150 mV which is about 140 mV more negative compared with unmodified SPE. Under optimized conditions, the modified electrode exhibited a linear response over the concentration range from 0.15 to 300.0 μM, with a detection limit of 0.08 μM (S/N = 3). The proposed sensor exhibited a high sensitivity, good stability and was successfully applied for dopamine determination in dopamine ampoule, with high recovery.